Geregtigheid, billikheid en waarheid in Platoniese en hedendaagse perspektief: Antieke waardes in Suid-Afrikaanse konteks - S.c, Deon van Zyl (Koers, 1999)
Justice, fairness and truth In Platonic and contemporary perspective: ancient values in South African contextThe concept of justice (dikaiosyne) in the thought of Plato was only one of the four cardinal virtues described by him, the others being wisdom (sophia), restraint (sophrosyne) and courage (andreia). Justice was inevitably linked with fairness or equity (epieikeia), a concept more fully developed by Plato's most famous pupil, Aristotle. It was likewise associated with the concept of truth (aletheia) as a virtue and as part of a purifying process. Later generations ofphilosophers, from Cicero to Rawls, were fascinated by such Platonic and Aristotelian thought, although they interpreted it in various ways. In a changing world many ancient values are as relevant today as they were in the distant past. They are basic to fundamental human rights, which have become so prominent in modern times. They are essential ingredients of peace and reconciliation, as amply recognised in South Africa, which has only recently joined the community of democratic nations and is dependent on instruments, such as its new Bill o f Rights and the Truth and Reconciliation Commission, to achieve transformation.